Quality of Yeast Extract of Industry Yeast Press Alcohol waste as Drying result with Various Temperature Variation - G. Maria Yusta; V. Irene Meitiniarti; E.B.E. Kristiani (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2016)
The content of yeast in industrial solid waste fermented beverages, has not been widely noticed and utilized, whereas many sources of nitrogen, vitamins and minerals are still present in this yeast. One of the utilization of waste yeast is processed into autolysis yeast extract. The drying process is often done using a spray dryer, but the process is costly so it is not efficient. In this study, we want to determine the temperature and drying time appropriate for maintain of yeast extract quality of yeast press. From this research, we concluded that a drying oven at 60 ° C for 6 hours is drying which does not damage the nutrient (protein, vitamine B2, carbohydrate, prolin, and lysin content) in yeast extract.©2016 JNSMR UIN Walisongo. All rights reserved.